THE NOVEL BY P. ANDREEVSKY “WHEAT-GRASS” AND THE SPIRITUAL TRADITIONS OF THE NATIONAL CULTURE (Philological Studies, 2019)
The article considers structure and images in the novel of the Macedonian writer P. Andreevsky. Also its place in Macedonian culture and its connection with spiritual traditions of Slavic literature are explored in the article.
Keywords: P. Andreevsky, Macedonia, culture, spiritual traditions, hagiography